Study of Granitoid Distribution at Toboali Waters, Bangka Belitung Province: Seismic data interpretation approach - Muhammad Zulfikar; Noor Cahyo Dwi Aryanto; Andi Agus Nur; Ildrem Syafri (BULLETIN OF THE MARINE GEOLOGY, 2020)
Bangka Island is one of the islands in Indonesia which is traversed by Southeast Asia granitoid belt. This belt stretches from Burma (Myanmar) to Bangka Belitung. This granitoid has potential as a source rock of mineral that carrying tin and rare earth element. At present, mapping of granitoid rocks to the waters area is rarely published, so acoustic basement mapping is necessary to do in order to determine the distribution of granitoids in Toboali waters. The research method used is a single channel seismic with an energy source of 300 joules. The sound source uses a single plate boomer, so it has a high enough resolution but the penetration is not deep enough. Acoustic basement in Toboali waters varies in depth from 15 - 75 ms or getting deeper south. When viewed from the continuity of the acoustic basement, it is estimated that the granitoid is 7 km from the nearest coastline.Key words: single channel seismic, seismic interprtation, granitoid distribution, Toboali Waters, Bangka Belitung ProvincePulau Bangka merupakan salah satu pulau di Indonesia yang dilalui oleh jalur granitoid Asia Tenggara. Jalur ini membentang dari Burma (Myanmar) hingga Bangka Belitung. Granitoid ini memiliki potensi sebagai batuan sumber pembawa mineral timah dan unsur tanah jarang. Pada saat ini pemetaan batuan granitoid pada daerah perairan jarang dipublikasikan, sehingga pemetaan batuan dasar akustik perlu dilakukan dalam rangka mengetahui sebaran granitoid di Perairan Toboali. Metode penelitian yang digunakan yaitu seismik single channel dengan sumber energi yang dikeluarkan sebesar 300 joule. Sumber suaranya menggunakan boomer single plate, sehingga memiliki resolusi yang cukup tinggi akan tetapi penetrasinya tidak cukup dalam. Batuan dasar akustik di Perairan Toboali memiliki kedalaman bervariasi mulai dari 15 – 75 ms atau semakin ke selatan semakin dalam. Jika dilihat dari kemenerusan batuan dasar akustiknya diperkirakan granitoid tersebut berada 7 km dari garis pantai terdekat.Kata kunci: Seismik single channel, interpretasi seismik, distribusi granitoid, Perairan Toboali, Provinsi Bangka Belitung